Energy Intake And Wasting Among Children Aged 6-59 Months - Ramadhani, Ni Shafa Khalishah Salsabila; Sudiarti, Trini; Syafiq, Ahmad (JKM (Jurnal Kebidanan Malahayati), 2025)
Background: Wasting is a malnutrition based on low body weight to height. Children are an age group that is more susceptible to wasting compared to other age groups. Wasting can be one of the main causes of morbidity and mortality. The prevalence of children experiencing wasting in Depok City in 2016 was 6.1%.Purpose:  to determine energy intake and other factors related to wasting in Bojongsari Subdistrict, Depok City.Methods:  The research sample was taken from the research population that met the inclusion and exclusion criteria. The inclusion criteria for the study were children aged 6-59 months and children with a z-score >-3 SD - 1SD who live in Bojongsari District, Depok City. While the exclusion criteria were children aged 6-59 months who had a z-score <-3 SD. So that the number of samples obtained was 251 children taken using non-probability sampling with a total sampling method. Data that met the criteria in the study were entered into the IBM SPSS program. Data analysis used the Chi-square test to analyze the relationship between the dependent variable and the independent variable with a statistical significance test using a p value <0.05. Multivariate logistic regression analysis to obtain the dominant factor in the incidence of wasting.Results: The nutritional status was 9.6% of children experienced wasting. The results of multivariate analysis showed that energy intake was the dominant factor in wasting in children aged 6-59 months (p-value 0.035).Conclusion: Children with insufficient energy intake had a 6.2 times greater risk of wasting compared to children with sufficient energy intake.Suggestions:  The results of the study are expected to be further specific and sensitive interventions in addressing factors related to improving malnutrition in children and it is necessary to conduct educational programs for mothers of children to introduce the form of complementary foods, the frequency of feeding, and continue the program of providing additional food to children who experience wasting.